2004
DOI: 10.1038/sj.sc.3101580
|View full text |Cite
|
Sign up to set email alerts
|

Role of NMDA receptor activation in serotonin agonist-induced air-stepping in paraplegic mice

Abstract: Study design: Experimental laboratory investigation of the effects of serotonergic and glutamatergic drugs in early paraplegic mice. Objectives: To examine whether NMDA and 5-HT receptors synergistically participate to generate basic stepping movements in paraplegic mice. Setting: Laval University Medical Center, Quebec, Canada. Methods: Adult mice completely spinalized at the low-thoracic level 1 week earlier were suspended in harnesses for experiments. Acute drug-induced effects were examined on hindlimb mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 28 publications
1
50
0
Order By: Relevance
“…Previous studies have shown that quipazine improves treadmill locomotion in adult chronic spinal cats (Barbeau and Rossignol, 1990;Brustein and Rossignol, 1999) and rats (FeraboliLohnherr et al, 1999;Antri et al, 2002), and recently, similar findings were reported for spinal mice (Guertin, 2004). We hypothesized that quipazine acutely elevates the sensitivity of the spinal locomotor circuits to proprioceptive inputs, thereby facilitating locomotor drive patterning when the spinal cord is presented with appropriate sensory cues.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies have shown that quipazine improves treadmill locomotion in adult chronic spinal cats (Barbeau and Rossignol, 1990;Brustein and Rossignol, 1999) and rats (FeraboliLohnherr et al, 1999;Antri et al, 2002), and recently, similar findings were reported for spinal mice (Guertin, 2004). We hypothesized that quipazine acutely elevates the sensitivity of the spinal locomotor circuits to proprioceptive inputs, thereby facilitating locomotor drive patterning when the spinal cord is presented with appropriate sensory cues.…”
Section: Introductionmentioning
confidence: 68%
“…Data to date suggest, however, that, in the absence of any pharmacological intervention, the level of recovery is lower in smaller species such as rats (de Leon et al, 2002) and mice (Guertin, 2004) compared with cats. Although there is one report of significant spontaneous recovery in complete spinal mice without any pharmacological intervention (Leblond et al, 2003), we have been unable to duplicate these observations.…”
Section: Introductionmentioning
confidence: 99%
“…All mice were spinal cord Tx at the low-thoracic level. [16][17][18] In brief, preoperative care included subcutaneous injection of 1 ml lactate-Ringer's solution, an analgesic (0.1 mg/kg buprenorphine) and an antibiotic (5 mg/kg Baytril). A complete transection of the spinal cord was performed intervertebrally using microscissors inserted between the 9th and 10th thoracic vertebrae in mice under complete anesthesia with 2.5% isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, administration of agonists selectively binding serotonergic receptors 2A/2C (5-HTR 2A/2C ) was found to acutely induce locomotor-like movements in hindlimbs of adult mice completely transected at the low-thoracic level. 11 This effect was shown to be blocked by selective 5-HT 2 or N-methyl-d-aspartate receptor antagonists suggesting a combined role for these subtypes of serotonergic and glutamatergic receptors in CPG activation. Using other 5-HT receptor agonists, additional experiments have provided evidence of a more specific role for the 5-HTR 2A rather than for the 5-HTR 2C receptors in spinal stepping generation.…”
mentioning
confidence: 99%
“…14,15 In brief, the use of wild-type and mutant paraplegic mouse models may assist scientists in understanding further the complex pathology of SCI. Recent development of less invasive approaches for surgery on mice (ie, with no laminectomy) [11][12][13][14][15][16] and of functional assessment methods adapted for small-size animals 17,18 will undoubtedly further facilitate the use of murine models in SCI research. This relatively new direction in SCI research will hopefully increase the number of significant findings in supporting the development of more effective therapies for SCI patients.…”
mentioning
confidence: 99%